2004
DOI: 10.1086/380600
|View full text |Cite
|
Sign up to set email alerts
|

ChandraPhase‐resolved X‐Ray Spectroscopy of the Crab Pulsar

Abstract: We present the first phase-resolved study of the X-ray spectral properties of the Crab pulsar that covers all pulse phases. The superb angular resolution of the Chandra X-Ray Observatory enables distinguishing the pulsar from the surrounding nebulosity, even at pulse minimum. Analysis of the pulse-averaged spectrum measures interstellar X-ray extinction due primarily to photoelectric absorption and secondarily to scattering by dust grains in the direction of the Crab Nebula. We confirm previous findings that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 33 publications
(70 reference statements)
3
59
0
Order By: Relevance
“…Before doing so, it is worth stressing that while we quote values of N H , our measurements are of the neon and magnesium (and oxygen for 4U 0142+61) column densities. Thus, the accuracy with which we can determine columns of a given other element (or dust) depends not only on our statistical uncertainty, but also on the uncertainty on the abundance of that element relative to neon and magnesium (as well as on possible corrections for the extent to which a given element is locked up in optically thick dust; e.g., Wilms et al [2000]; for a general caution on the implications of the set of abundances used, see Weisskopf et al [2004]). …”
Section: Resultsmentioning
confidence: 99%
“…Before doing so, it is worth stressing that while we quote values of N H , our measurements are of the neon and magnesium (and oxygen for 4U 0142+61) column densities. Thus, the accuracy with which we can determine columns of a given other element (or dust) depends not only on our statistical uncertainty, but also on the uncertainty on the abundance of that element relative to neon and magnesium (as well as on possible corrections for the extent to which a given element is locked up in optically thick dust; e.g., Wilms et al [2000]; for a general caution on the implications of the set of abundances used, see Weisskopf et al [2004]). …”
Section: Resultsmentioning
confidence: 99%
“…This plot also shows that O abs is significantly different from solar. Weisskopf et al (2004) report from their Chandra observation of the Crab nebula that, using the abundances from Anders & Grevesse (1989), they find an underabundance of oxygen in the Galactic absorption component of 0.41 ± 0.07. Takei et al (2003) find values in the range from 0.63 ± 0.12 to 0.74 ± 0.14 using a Chandra observation of Cyg X-2.…”
Section: Discussionmentioning
confidence: 99%
“…The low metal content of LMC, and the low MW foreground absorption, make such tests sensitive to any supernova ejecta contribution. X-ray spectral fits to data obtained with Chandra of the Crab pulsar have recently highlighted the importance of the abundance factor (Willingale et al 2001;Weisskopf et al 2004). Using various abundances it was found that the line of sight to the Crab is significantly underabundant in oxygen.…”
Section: Supernova Ejecta Absorptionmentioning
confidence: 99%